Criticism of Hadiths on Earning a Livelihood: Compilation of Hadiths from the book “Islah al-Hal bi Thalab al-Halal” by Habib Utsman al-Batawi - Nurhakim, Amien; Fatihunnada, Fatihunnada (Al-Bukhari : Jurnal Ilmu Hadis, 2023)
Hadith has an essential role in the ethical guidelines for seeking halal sustenance. This article aims to trace the validity and quality of the hadith in Sayyid Utsman al-Batawi's work entitled "Islah al-Hal bi Thalab al-Halal", a book that discusses virtues and prohibition of people lawfully seeking sustenance with hadiths of the Prophet as its validation. The method used in this article is the Takhrij method by al-'Iraqi in his work "al-Mughni". The method involves citing hadith text, mentioning narrators from the Prophet's sahabah, and concisely listing the sources and qualities of hadith. The results are from 29 hadiths validating seeking halal sustenance in this book 19 hadiths have sahih quality, five hadiths have dha'if qualities, 17 hadiths have hasan quality, and two hadiths have not been judged due to lack of data and sources. On the other hand, the sources of hadith in this book are from Kutubuttis'ah and primary hadith books such as Mu'jam al-Thabrani and al-Mustadrak. Nevertheless, Sayyid Uthman did not appear to refer to these sources directly, but he quoted them from secondary references such as Ihya 'Ulumiddin by Imam al-Ghazali.